Immunotherapy in Cancer Management: A Literature Review of Clinical Efficacy of Pembrolizumab in the Non-small Cell Lung Cancer Treatment - Miquelotti, Luísa Biscaglia; Sari, Marcel Henrique Marcondes; Ferreira, Luana Mota (Advanced pharmaceutical bulletin, 2023)
Purpose: Cancer is a global public health problem that affects millions of people every year and the immunotherapy has been a promising alternative for its treatment. The aim of this study was to gather data concerning the efficacy and safety of immunotherapy in the treatment of non-small cell lung cancer (NSCLC), emphasizing pembrolizumb, a humanized antibody. This study also reports the role of immunotherapy in cancer treatments, contemplating the anti-CTLA4, anti-PD-L1 and anti PD-1 action in lymphocyte T cells. Methods: A bibliographic review was performed using Pubmed, SCIELO and SCOPUS databases, screening the scientific studies published within the last 5 years. Results: Seven clinical trials were selected to discuss the benefits of pembrolizumab as NSCLC therapy in untreated and previously treated patients, considering or not the tumor proportion score (TPS). It was found that NSCLC occurs with great frequency in Brazil and worldwide, presenting a poor prognosis due to its late diagnosis in most cases. Immunotherapy is a promising treatment strategy for NSCLC because its benefits overcome its risks compared to other therapies. Besides, the studies evidenced the efficiency of pembrolizumab as monotherapy or in association whit chemotherapy, in the first or second line of treatment and, additionally, patient’s whit TPS ≥ 50% seem to have a greater benefit from the treatment. Conclusion: The data collected herein showed that pembrolizumab is a very promising, effective, and safe treatment option against NSCLC. Lastly, it is important to highlight the relevance of review’s studies, since they are easy-to-read materials, collecting relevant information on a subject.